Recent Advances in Brachytherapy Using Radioactive Nanoparticles: An Alternative to Seed-Based Brachytherapy - Seniwal, Baljeet; Thipe, Velaphi C.; Singh, Sukhvir; Fonseca, Telma C. F.; Freitas de Freitas, Lucas (Frontiers in Oncology, 2021)
Interstitial brachytherapy (BT) is generally used for the treatment of well-confined solid tumors. One example of this is in the treatment of prostate tumors by permanent placement of radioactive seeds within the prostate gland, where low doses of radiation are delivered for several months. However, successful implementation of this technique is hampered due to several posttreatment adverse effects or symptoms and operational and logistical complications associated with it. Recently, with the advancements in nanotechnology, radioactive nanoparticles (radio-NPs) functionalized with tumor-specific biomolecules, injected intratumorally, have been reported as an alternative to seed-based BT. Successful treatment of solid tumors using radio-NPs has been reported in several preclinical studies, on both mice and canine models. In this article, we review the recent advancements in the synthesis and use of radio-NPs as a substitute to seed-based BT. Here, we discuss the limitations of current seed-based BT and advantages of radio-NPs for BT applications. Recent progress on the types of radio-NPs, their features, synthesis methods, and delivery techniques are discussed. The last part of the review focuses on the currently used dosimetry protocols and studies on the dosimetry of nanobrachytherapy applications using radio-NPs. The current challenges and future research directions on the role of radio-NPs in BT treatments are also discussed.